Reformas curriculares e a formação do (novo) trabalhador em Educação Física: a subsunção da formação à lógica privada/mercantil - Morschbacher, Márcia (2012)
This dissertation linked to the Research Line School, Training and Labour, of Pos Graduate Program in Physical Education, Federal University of Pelotas, has as central theme of study the employer training in Physical Education in brazilian capitalist society, in a determinated historical period this social formation from the advent of the National Curriculum Guidelines currently in effect. In this research, the objective is analyze the consequences of these legal orders in the worker‟s training in Physical Education from the viewpoint of the processes of curricular reform carried out in two Universities in Rio Grande do Sul state, the Federal University of Pelotas and the University Federal of Santa Maria. Using the contributions of Dialectical-Historical Materialism, with reference, was made a research descriptive-explanatory of source bibliographical and documentary, whose sources of information are the opinions by CNE/CP 09/2001 and CNE/CES 058/2004, the Resolution CNE/CP 01/2002 and CNE/CES 07/2004, the Pedagogical Projects of Bachelor Degree of Physical Education of the institutions mentioned and the records/minutes of its restructuring curriculum committees, departments and collegiate. The analytical process of documentary source was based on the relantionship between the Categories of Method, content and technique Social Analysis of Discourse. From the study of the current historical period marked by a profund crisis of accumulation and hegemony of the capitalist mode of production, peering up dissertation the social function of the processes of human development in the maintenance of the objective conditions of existence governed by the logic of capital. Later, lies the worker‟s training in Physical Education in capitalist society in the wake of the Brazilian historical period, asking it from the sandpoint of the legal requirements stemming from the National Curriculum Guidelines. It is evident that such domestic legal subsume the formation of such a worker to capital, to the extent that perspective from the fragmentation of the training and knowledge of the disqualification, employability, skills development, human movement as an object of study Physical Education, among other references. As part of the Pedagogical Projects of undergraduate courses in Physical Education of the institutions surveyed, is indicating the reproduction and/or uncritical appropriation of these legal determinations arising regulatory frameworks. These considerations represent important contributions to consider what the National Curriculum Guidelines, the Draft Course and of undergraduate courses in Physical Education are mediators elements between the capital and worker training in this area of knowledge, which tend subsume it to the private-market logic